2017
DOI: 10.3389/fmicb.2017.00549
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bacterial and Anti-biofilm Evaluation of Thiazolopyrimidinone Derivatives Targeting the Histidine Kinase YycG Protein of Staphylococcus epidermidis

Abstract: Staphylococcus epidermidis is one of the most important opportunistic pathogens in nosocomial infections. The main pathogenicity associated with S. epidermidis involves the formation of biofilms on implanted medical devices, biofilms dramatically decrease the efficacy of conventional antibiotics and the host immune system. This emphasizes the urgent need for designing novel anti-staphylococcal biofilm agents. Based on the findings that compound 5, targeting the histidine kinase domain of S. epidermidis YycG, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…YycG/YycF TCS regulates S. epidermidis biofilm formation ( Xu et al, 2017 ). Because inhibitors targeting the cytoplasmic HATPase_c domain of YycG exhibit anti-biofilm activity ( Qin et al, 2006 ; Huang et al, 2012 ; Liu et al, 2014 ; Lv et al, 2017 ), we generated mAbs against the extracellular domain of YycG (YycG ex , aa 34–184) of S. epidermidis RP62A, and from nine hybridoma lines, we selected for further investigation the two mAbs (2F3 and 1H1) that exhibited the highest affinity for the protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…YycG/YycF TCS regulates S. epidermidis biofilm formation ( Xu et al, 2017 ). Because inhibitors targeting the cytoplasmic HATPase_c domain of YycG exhibit anti-biofilm activity ( Qin et al, 2006 ; Huang et al, 2012 ; Liu et al, 2014 ; Lv et al, 2017 ), we generated mAbs against the extracellular domain of YycG (YycG ex , aa 34–184) of S. epidermidis RP62A, and from nine hybridoma lines, we selected for further investigation the two mAbs (2F3 and 1H1) that exhibited the highest affinity for the protein.…”
Section: Resultsmentioning
confidence: 99%
“…The YycG/YycF TCS is essential for bacterial growth and plays a major role in biofilm formation ( Fukuchi et al, 2000 ; Howell et al, 2003 ; Mohedano et al, 2005 ; Ahn and Burne, 2007 ; Bisicchia et al, 2007 ). YycG histidine kinase is a transmembrane protein, and we have shown that inhibitors that target the cytoplasmic HATPase_c domain of S. epidermidis exhibit bactericidal and biofilm-killing activities ( Qin et al, 2006 ; Huang et al, 2012 ; Liu et al, 2014 ; Lv et al, 2017 ). Previous studies have found that the extracellular domain of the protein (YycG ex domain) adopts a PAS fold predicted as a sensor of YycG by sensing environmental signals such as oxygen, light, redox potential, or the presence of specific ligands ( Taylor and Zhulin, 1999 ; Santelli et al, 2007 ; Chang et al, 2010 ; Shah et al, 2013 ; Kim et al, 2016 ), but little is known of the nature of the signals and factors sensed by YycG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…epidermidis and S. aureus. ,, In this study, the highly conserved sequence of the YycFG TCS in these bacterial species supported the designing of molecules targeting its HK for the development of novel antibacterial drugs against E. faecalis.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…(20) Also, it has been shown in some patients with PBC that there is depletion of the nonpathogenic bacteria useful to the body to the benefit of pathogenic and opportunistic bacteria such as Veillonella and Streptococcus. (21) Recently, some therapies referring to fecal microbiota transplantation (FMT) have emerged. FMT consists of introducing beneficial commensal bacteria into the gut of patients with diseases whose gut dysbiosis plays a role in the initiation and progression.…”
Section: Hypothesis: Trained Immunity Contributes To the Pathogenesis Of Cholangiopathies Translocation Of Microorganismsmentioning
confidence: 99%